Implementation Process of Research Based Learning (RBL) for Doctoral Education Program Students: An Exploratory Case Study - Yanti, Fitri April; Ruyani, Aceng; Yunitasari, Yunitasari; Thohir, M. Anas; Kinasih, Ayang (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
Research-based learning (RBL) is a learning model that involves research activities in the learning process. The higher education system cannot separate from learning and research activities. This study aims to present a case study that explores the learning experiences of 5 students of the doctoral education program and how their research skills differ before and after implementing RBL in a local-based science learning development course. Collecting data methods are interviews, learning notes, product assessments, and questionnaires. Data analysis consisted of examining, categorizing, and recombining the quantitative and qualitative evidence to discuss the research's initial propositions. Research results show that the ability of doctoral program students applied knowledge in practical contexts, research skills, critical and analytical thinking, scientific communication skills could be improved through research-based learning.